The role of Qishen Yiqi dripping pills in treating chronic heart failure: An overview of systematic reviews and meta-analyses - Chen, Wensheng; Chen, Jiezhen; Wang, Yuanping; Yan, Jiaqi; Yan, Xia; Wang, Dawei; Liu, Yuntao (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objectives: Evidence from systematic reviews/meta-analyses on the efficacy and safety of Qishen Yiqi (QSYQ) dripping pills for the treatment of chronic heart failure (CHF) remains unclear. To assess the reliability of the evidence and to provide reliable information for the clinical use of QSYQ, a comprehensive review of the available systematic reviews was conducted. Methods: Systematic reviews were systematically collected by searching six major medical databases. The included studies were evaluated in terms of methodological quality and quality of evidence using criteria from the Assessment of Multiple Systematic review 2 (AMSTAR-2) tool, and the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) system, respectively. Results: Overall, 14 systematic reviews were included in our overview, from which it was concluded that QSYQ combined with conventional medicine (CM) treatment had greater advantages than CM treatment alone in terms of improving cardiac function-related indices (e.g., increasing the left ventricular ejection fraction (LVEF), reducing the left ventricular end-diastolic dimension (LVEDD), and left ventricular end-systolic internal diameter (LVESD)), improving the total effective rate and six-minutes walking distance (6MWD), and reducing N-terminal pro-brain natriuretic peptide (NT-proBNP). Furthermore, no QSYQ-related adverse effects were observed. However, the GRADE results showed “very low” to “moderate” evidence for these outcomes, with no high-quality evidence to support them. According to the AMSTAR-2, all systematic reviews were considered to be of “critically low” quality, limited mainly by deficiencies in the following areas: registration of study protocols, explanation of the inclusion of randomized controlled trials (RCTs), complete and detailed search strategy, list of excluded literature, description of funding sources for inclusion in RCTs, investigation of the impact of risk of bias on the results of meta-analysis, and reporting of potential conflicts of interest. Conclusion: Systematic reviews of QSYQ for CHF have “critically low” methodological quality, and there are common areas for improvement. The efficacy and safety of QSYQ adjuvant therapy for CHF remain to be further demonstrated due to the lack of high-quality evidence provided by current systematic reviews.